Ochratoxin A: Occurrence and recent advances in detoxification - Wang, Lan; Hua, Xia; Shi, Jie; Jing, Ninghao; Ji, Ting; Lv, Bing; Liu, Lijun; Chen, Yun (Toxicon (Oxford), 2022)
Ochratoxin A (OTA), one of the most important mycotoxins, is mainly produced by fungi in the genera Aspergillus and Penicillium, and commonly found in food and agricultural products. In addition to causing significant economic losses, the occurrence of OTA in foods poses a serious threat to human health. Therefore, it is very important to develop approaches to control or detoxify OTA contamination and thus ensure food safety. In this paper, we review the source and occurrence of OTA in food and agricultural products and the latest achievements in the removal and detoxification of OTA using physical, chemical, and biological methods, with specific attention to influencing factors and mechanisms related to the biodetoxification of OTA. Moreover, the advantages and disadvantages of these methods and their potential application prospect were also discussed. [Display omitted] •Ochratoxin A is a mycotoxin mainly produced by Aspergillus and Penicillium spp.•Ochratoxin A contamination occurs in a wide range of food and agricultural commodities.•Physical, chemical, and biological methods have been used in ochratoxin A detoxification.•Biological degradation or transformation has great potential in ochratoxin A detoxification.